Petrogenesis of lherzolites from the Purang ophiolite, Yarlung-Zangbo suture zone, Tibet: origin and significance of ultra-high pressure and other 'unusual' minerals in the Neo-Tethyan lithospheric mantle. Issue 17 (22nd November 2019) - Xiong, Fahui; Liu, Zhao; Kapsiotis, Argyrios; Yang, Jingsui; Lenaz, Davide; Robinson, Paul T.
ABSTRACT: The Purang ultramafic massif, located in the Yarlung-Zangbo Suture Zone (YZSZ) of the Tibetan Plateau, consists mainly of harzburgites and minor lherzolites. The spinel-bearing lherzolites of the NW part of the massif display a granular texture, consisting of large olivine and pyroxene crystals with curvilinear grain boundaries. These lherzolites contain chromian spinel (Cr-spinel) of low Cr# [100 × Cr/(Cr +Al) = 24.7–30.2], enstatite with high Mg# [100 × Mg/(Mg + Fe 2+ ) = 90.0–91.2] and relatively high Al2 O3 content (3.3–4.1 wt%), and diopside with high Mg# (90.2–93.3) and Al2 O3 content (4.6–5.0 wt%). These compositions are analogous to those of spinel and pyroxenes from residual peridotites. However, the Purang lherzolites show U-shaped primitive mantle (PM)-normalized rare earth element (REE)-profiles, which are not consistent with a potential origin as melting residues. The high LREE contents and positive Ti anomalies shown by the investigated lherzolites coupled with the low TiO2 content of their mineral constituents imply that these rocks possibly stored LREE- and Ti-bearing arc-related melts/fluids in their groundmass. A mineral assemblage composed of diamond, super-reduced [(SuR) moissanite, native Cr] and crustal-derived minerals (zircon, corundum, rutile), has been separated from the Purang lherzolites. Uranium-Pb geochronological dating of zircons yielded an age range between 1718 and 465 Ma, indicating that they represent ancient crustal material delivered into the upper mantle via previous subduction events. Diamonds and old zircons (± crustal minerals) were carried to shallow mantle levels by asthenospheric magmas produced during a slab rollback-induced decompression melting process. The recovery of SuR minerals is consistent with fluid percolation and crystallization of alteration-related minerals in the lithospheric parts of a (hydrated) mantle wedge, resulting in the formation of highly reduced micro-environments. Graphic abstract: